Controlled Removal of Surfactants from Double‐Walled Carbon Nanotubes for Stronger p‐Doping Effect and Its Demonstration in Perovskite Solar Cells. Issue 6 (22nd April 2021) - Shawky, Ahmed; Nam, Jeong‐Seok; Kim, Kyusun; Han, Jiye; Yoon, Jungjin; Seo, Seungju; Lee, Chang Soo; Xiang, Rong; Matsuo, Yutaka; Lee, Hyuck Mo; Maruyama, Shigeo; Jeon, Il
Abstract: Double‐walled carbon nanotubes (DWNTs) have shown potential as promising alternatives to conventional transparent electrodes owing to their solution processability as well as high conductivity and transparency. However, their DC to optical conductivity ratio is limited by the surrounding surfactants that prevent the p‐doping of the DWNTs. To maximize the doping effectiveness, the surfactants are removed from the DWNTs, with negligible damage to the nanotubes, by calcination in an Ar atmosphere. The effective removal of the surfactants is characterized by various analyses, and the results show that the optimal calcination temperature is 400 °C. The conductivity of the DWNTs films improves when doped by triflic acid. While the conductivity increase of the surfactants‐wrapped DWNT films is 31.9%, the conductivity increase of the surfactants‐removed DWNT is found to be 59.7%. Using the surfactants‐removed, p‐doped, solution‐processed transparent electrodes, inverted‐type perovskite solar cells are fabricated, resulting in a power conversion efficiency of 17.7% without hysteresis. This work advances the application of DWNTs in transparent conductors, as the efficiency obtained is the highest value achieved to date for carbon nanotube electrode‐based perovskite solar cells and solution‐processable transparent electrode‐based solar cells. Abstract : Surfactant‐removal from a solution‐processed, double‐walled carbon nanotube film by thermal treatment in an argon atmosphere enables strong chemical p‐doping. Calcinating the nanotubes at 400 °C effectively removes the surfactants with minimal damage to the nanotubes, increasing the doping effectiveness from 31.9% to 59.7%. The enhanced p‐doping effect is investigated via perovskite solar cell application. The efficiency increases from 16.6% to 17.7%.